Issues of Cybersecurity of The Production System - Maradová, Karla; Blecha, Petr; Blecha, Radim; Rozehnalová, Jana; Frkal, Vojtěch (MM Publishing, 2022)
Cybersecurity of production systems is a very topical issue in response to the dangers associated with the very high number of cyber-attacks in Europe. The current digital transformation of the industry associated with the digitalisation of manufacturing brings both the positives associated with increased flexibility and productivity of production, and the negatives associated with the risk of data loss, data alteration or blocking of control systems. Cybersecurity issues are also reflected in the revision of EU harmonisation legislation governing the requirements for placing products on the market or in service. It appears that the issue of cyber security needs to be addressed comprehensively across the entire infrastructure of a manufacturing plant. The present paper focuses on the relationship between machinery security and OT/IT security and presents the results of a study aimed at identifying potential sources of threats in an integrated manufacturing system.

Cybersecurity of production systems is a very topical issue in response to the dangers associated with the very high number of cyber-attacks in Europe. The current digital transformation of the industry associated with the digitalisation of manufacturing brings both the positives associated with increased flexibility and productivity of production, and the negatives associated with the risk of data loss, data alteration or blocking of control systems. Cybersecurity issues are also reflected in the revision of EU harmonisation legislation governing the requirements for placing products on the market or in service. It appears that the issue of cyber security needs to be addressed comprehensively across the entire infrastructure of a manufacturing plant. The present paper focuses on the relationship between machinery security and OT/IT security and presents the results of a study aimed at identifying potential sources of threats in an integrated manufacturing system.
Issues of Cybersecurity of The Production System
Keywords: Cyber security; threat; integrated production system; prevention; cyber-attack; infrastructure; Cyber security; threat; integrated production system; prevention; cyber-attack; infrastructure